Breach Remedies Including Hybrid Investments - Daniel Göller; Alexander Stremitzer (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2009)
We show that parties in bilateral trade can rely on the default common law breach remedy of 'expectation damages' to induce simultaneously ?rst-best relationship-speci?c investments of both the sel?sh and the cooperative kind. This can be achieved by writing a contract that speci?es a suffciently high quality level. In contrast, the result by Che and Chung (1999) that 'reliance damages' induce the ?rstbest in a setting of purely cooperative investments, does not generalize to the hybrid case. We also show that if the quality speci?ed in the contract is too low, 'expectation damages' do not necessarily induce the ex-post effcient trade decision in the presence of cooperative investments.
urn:nbn:de:bvb:19-epub-13272-0
Keywords: 330; breach remedies; incomplete contracts; hybrid investments; cooperative investments; sel?sh investments